8. RETHINKING MICROFINANCE DEVELOPMENT IN INDONESIA - Ketut Budastra (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2018)
Abstract This paper analyzes the microfinance policies in Indonesia, focusing on two issues: the extent to which the microfinance system in Indonesia had been liberalized and whether liberalized financial policies alone is a sufficient condition for microfinance development. In the attempts the financial policies with relevant implications to microfinance development (introduced from 1983-2000) in Indonesia were reviewed and the likely impacts of the financial liberalization were explored. The analysis shows that most of the repressive elements of the previous policies on the microfinance system has been abolished. In spite of that, the number and the scale of credit programs remained substantial. The linear reasoning of the financial liberalization proponents’ expectation might not realize as there are also other factors that affect the dinamics of the microfinance market. Among these factors are the characteristics of the finanscal institutions and the households, the economic condition. Thus, financial liberalication is an insufficient condition for microfinance developmen. Microfinance development should be done in tandem with economic, tecnical, institutional, and infrastructure development. The formulation of financial policies should take into account information from both the demand and supply sides of the microfinance market. ABSTRAK Paper ini menganalisa peraturan-perundangan dan kebijakan pembiayaan mikro di Indonesia, dengan menitikberatkan pada dua issu, yakni: sejauh mana sistim pembiayaan mikro telah diliberalisasi dan apakah perbaikan perbaikan peraturan-perundangan dan kebijakan saja sudah cukup untuk membangun sektor pembiayaan mikro. Dalam upaya itu, paper ini menganalisa peraturan-perundangan dan kebijakan sektor keuangan yang memiliki implikasi pada pembangunan sektor pembiayaan mikro di Indonesia dalam kurun waktu 1983-2000. Kemungkinan hasilnya dalam mengembangkan sektor pembiayaan mikro juga ditelusuri. Analisis peraturan-perundangan dan kebijakan menemukan bahwa sebagian besar elemen-elemen peraturan-perundangan dan kebijakan yang menghambat perkembangan sistim pembiayaan mikro di Indonesia telah dihapuskan. Meskipun demikian sistim pembiayaan mikro itu masih belum sepenuhnya liberal karena jumlah dan skala credit programs masih relatip besar walaupun kegagalan kredit program acapkali dilaporkan dalam media. Peraturan-perundangan dan kebijakan demikian diharapkan akan meningkatkan skala dan effisiensi pelayanan dari sistim pembiayaan mikro di Indonesia. Hasil demikian mungkin tak menjadi kenyataan, karena terdapat faktor-faktor lain selain peraturan-perundangan dan kebijakan yang berpengaruh seperti karakteristik lembaga pembiayaan mikro. Pembangunan sektor pembiayaan mikro hendaknya dilakukan seiring dengan pengembangan sektor ekonomi, teknologi, kelembagaan dan infrastruktur. Formulasi kebijakan sektor pembiayaan mikro hendaknya mempertimbangkan baik sisi permintaan maupun sisi penawaran dalam pasar pembiayaan mikro.